Pengembangan Sistem Informasi Pengajuan Judul Skripsi Menggunakan Algoritma Winnowing - Armiady, Dedy (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2023)
Administrative implementation in higher education institutions is currently increasingly directed to completely transform into digital-based administration by utilizing computer-based technology. It is intended that all forms of administrative services can be neatly arranged and easy to access. One case that has also become a concern for development is the case of submitting a student thesis title. Currently, many systems are being developed just for CRUD (Create, Read, Delete and Update) needs. Where in the old system, there was no similarity detection feature for proposed titles with existing titles. This study aims to build a system for submitting thesis titles for students of the Faculty of Computer Science, Almuslim University which has a title check similarity feature. In this study, the winnowing algorithm is used as a mathematical calculation model to calculate the proportion of document similarities using the document fingerprint method. The developed system is a web-based information system using the PHP and MySQL programming languages. As for the results obtained, the winnowing algorithm can be applied to a title submission information system that can display the proportion of the proposed title to the existing title